the Use Of Politcal Information In The Media:a Study On Illegal Migration In Magreb - Hadir, Mohamed (Afak For Sciences, 2024)
In the 21st century, information has become a sculptor, meticulously crafting narratives and shaping public discourse around sensitive topics like illegal migration. Media outlets, once perceived as neutral platforms, are now wielding this chisel with increasing frequency, their strokes driven by political agendas or opportunistic exploitation of uncertainties. In the Maghreb region, this manipulation paints a stark picture: migrants morph into "enemies at the gate," threatening to invade Western nations. But beneath the surface of sensational headlines and carefully curated narratives lies a more complex reality. This study ventures into the tangled web of internet, media, and the illegal migration crisis in the Maghreb. We dissect the media's influence on public perception, scrutinize how governments leverage social media for intrusive surveillance, and expose the opaque tactics of internet censorship employed by host countries. Yet, our journey doesn't end there. We delve into crucial questions: how does media sculpt the political landscape surrounding migration pressure? Can we predict future migration flows based on the Maghreb context? By seeking answers, we aim to build a model that not only understands the past but anticipates the future. A future where migration is viewed with empathy and understanding, not manipulated with fear and division. . ملخص: أصبحت المعلومات بمثابة نحات في القرن الحادي والعشرين، يصوغ الروايات بدقة ويشكل الخطاب العام حول مواضيع حساسة مثل الهجرة غير الشرعية. إن وسائل الإعلام، التي كان يُنظر إليها ذات يوم على أنها منصات محايدة، أصبحت الآن تستخدم هذا الإزميل بوتيرة متزايدة، مدفوعة بأجندات سياسية أو استغلال انتهازي للشكوك. وفي منطقة المغرب العربي، يرسم هذا التلاعب صورة صارخة: حيث يتحول المهاجرون إلى "أعداء على البوابة"، ويهددون بغزو الدول الغربية. لكن تحت سطح العناوين المثيرة والروايات المنسقة بعناية تكمن حقيقة أكثر تعقيدًا. تتناول هذه الدراسة الشبكة المتشابكة للإنترنت ووسائل الإعلام وأزمة الهجرة غير الشرعية في منطقة المغرب العربي. نحن نحلل تأثير وسائل الإعلام على التصور العام، وندقق في كيفية استفادة الحكومات من وسائل الإعلام الاجتماعية للمراقبة التدخلية، ونكشف عن التكتيكات الغامضة للرقابة على الإنترنت التي تستخدمها البلدان المضيفة. ومع ذلك، رحلتنا لا تنتهي عند هذا الحد. نحن نتعمق في أسئلة حاسمة: كيف تقوم وسائل الإعلام بنحت المشهد السياسي المحيط بضغوط الهجرة؟ هل يمكننا التنبؤ بتدفقات الهجرة المستقبلية بناء على السياق المغاربي؟ ومن خلال البحث عن إجابات، نهدف إلى بناء نموذج لا يفهم الماضي فحسب، بل يتوقع المستقبل. مستقبل يُنظر فيه إلى الهجرة بالتعاطف والتفاهم، وليس بالخوف والانقسام.الكلمات المفتاحية: معلومات سياسية؛ الإعلام؛ الهجرة غير الشرعية؛ المغرب العربي.
Volume 9, Numéro 2, Pages 219-253
Keywords: Informations; olitical.magreb..migration.illigal